Evaluation of placental growth factor, Vitamin D, and systemic inflammatory index as predictive biomarkers for preeclampsia severity: a retrospective cohort study - Xiaoyan Han; Hua Yang (BMC Pregnancy and Childbirth)
Abstract Aim Our study aimed to evaluate the predictive value of Placental growth factor (PlGF), Vitamin D, and systemic inflammatory index for assessing preeclampsia risk and severity. Materials and methods This retrospective cohort study included 457 pregnant individuals who delivered at our hospital between March 2023 and October 2024. Participants were divided into three groups: control (n = 217), mild preeclampsia (n = 101), and severe preeclampsia (n = 67). A separate validation cohort (n = 72) was used to test model performance. Data on demographic, clinical, and laboratory characteristics, including PlGF, Vitamin D, neutrophil, lymphocyte, and monocyte counts, were collected between 16 and 20 weeks of gestation. Logistic regression analysis was performed to identify independent risk factors, and receiver operating characteristic (ROC) curve analysis was used to assess the predictive power of PlGF, Vitamin D, lymphocyte count, and Pan-immune-inflammation value (PIV). The regression models adjusted for potential confounders, including maternal age, body mass index (BMI), and parity. Results In the training cohort, significant differences were observed among control, mild, and severe preeclampsia groups, with severe cases showing elevated PIV (515.8 ± 126.7) and reduced levels of PlGF (12.5 ± 5.8 pg/mL) and Vitamin D (8.4 ± 1.9 ng/mL) compared to controls (P < 0.001). Logistic regression identified lower levels of PlGF (P < 0.001) and Vitamin D (P < 0.001) as significant independent risk factors for severe preeclampsia. PIV was also a strong predictor, showing a high hazard ratio (P < 0.001). In the training and validation cohorts, ROC analysis showed AUC values of 0.774 and 0.751 for PlGF, 0.805 and 0.796 for Vitamin D, 0.688 and 0.675 for Lymphocyte, and 0.724 and 0.752 for PIV, respectively, indicating strong predictive value for PlGF, Vitamin D, and PIV in assessing preeclampsia risk. Conclusion Lower levels of PlGF and Vitamin D, along with higher PIV, were independently associated with an increased risk of severe preeclampsia. These findings suggest that PlGF, Vitamin D, and PIV are valuable biomarkers for early identification of high-risk preeclampsia patients, potentially aiding in timely intervention and improved outcomes.